Report of the Economic Administration Reforms Commission on Government and Public Enterprises - Planning Commission (Planning Commission, 1985)
The performance of public enterprises has attracted a good deal of attention—and criticism— over the years. In the recent past there has been growing concern over the low returns on the huge investments made in the public sector. There have been studies by Committees and Commissions, discussions in seminars and conferences, Audit Reports by the Comptroller and Auditor General of India and reports by Parliamentary Committees, dealing with different aspects of the performance of public enterprises. the present Commission does not intend to cover the same ground as the previous studies. Our focus instead will be essentially on the impact of the government machinery on public enterprises. Government rules, policies and procedures which apply to the public sector, over and above those which apply to the private sector as well, and the need to obtain governmental clearance (formally or informally) prior to the implementation of decisions taken by
Bureau of Public Enterprises (Ministry of Finance) Government of India